Acute effects of THC and a CBD+THC combination on cardiovascular haemodynamics and respiratory muscle activity during loaded breathing in healthy adults: A randomized placebo‐controlled crossover study - Edna Karla Ferreira Laurentino; Marina Lyra L. C. Fagundes; Bruno Lobão Soares; Rodrigo Torres‐Castro; Matias Otto‐Yañez; Emerson Arcoverde Nunes; Matheus Freitas Fernandes Pedrosa; Jéssica Danielle Medeiros da Fonsêca; Vanessa R. Resqueti; Guilherme Augusto de Freitas Fregonezi (British Journal of Clinical Pharmacology, 2026)
Aims This study aimed to evaluate the acute effects of cannabidiol plus tetrahydrocannabinol (CBD+THC) and tetrahydrocannabinol (THC) oils on cardiovascular haemodynamics, respiratory muscle activity and peripheral tissue perfusion in healthy adults. Methods In this randomized, double‐blind, crossover trial, participants received orally administered CBD+THC oil (12.5 mg + 12.5 mg), THC oil (12.5 mg) or placebo. Cardiovascular haemodynamics, respiratory muscle electromyography and peripheral tissue perfusion were evaluated during breathing tasks. Results Eighteen individuals were evaluated (26 ± 5 years). Both oils significantly increased heart rate (HR) ( p < 0.05). Cardiac index significantly increased in I‐THC at 60 and 150 min postdose ( p < 0.05). The vascular resistance index was lower in the I‐THC, with significant differences during respiratory overload and recovery ( p < 0.05). A significant increase in activity of the sternocleidomastoid (SCM) and parasternal (PARA) muscles was observed in the I‐THC during inspiratory loading at 60 and 150 min after dose ( p < 0.05). In the I‐CBD+THC, increased activation was observed in the scalene (ESC) and PARA muscles ( p ≤ 0.021). HHb levels showed a descriptive decrease, particularly during inspiratory loading and recovery in the I‐THC group, without reaching statistical significance, whereas O 2 Hb showed a significant increase during inspiratory loading in the I‐THC group ( p < 0.05). Conclusions Acute administration of THC and CBD+THC oils induced distinct cardiorespiratory responses in healthy individuals, affecting cardiovascular haemodynamics, respiratory muscle activation and peripheral tissue oxygenation. THC produced more pronounced physiological responses, while CBD+THC was associated with a more attenuated pattern.